Comparative Study of Pulmonary Functions in Pre-Pubertal and Pubertal Girls - Bodat, Rajeshri K; Chaudhari, Snehalata J (National Journal of Community Medicine, 2015)
Introduction: During pregnancy, increase in alveolar ventilation and luteal phase is also well known and has been attributed to in- creased levels of progesterone. The study has reported pulmonary changes in pre-pubertal and pubertal girls. Methodology: The present cross-sectional study conducted among pre pubertal girls (10-12 yrs) and pubertal girls between age groups 13 to 18 yrs. Standard anthropometric measurements weight (kg), height (cm), was measured in a beam balance. Details history and minimum three readings were given and best of the three was cho- sen for analysis, based on standardization of spirometry study based on ATS/ERS task force series and various other studies. Result: mean age of the participants was 11.36 (±0.69) years in pre- pubertal girl and 15.3(±2.04) years in pubertal girls. Similarly mean height, weight, BMI (Body Mass Index) and BSA (Body Surface Area) was 134.8(±8.91) cm, 28(±5.9) kg, 15.29(±2.02) (Kg/m2), and 1.02(±0.13) (m2) in pre-pubertal girl and 153.13 (±9.77) cm, 39.44 (±7.27) kg, 16.67 (±1.95) (Kg/m2), and 1.29 (±0.15) (m2) in pubertal girl respectively. There were difference between respiratory pa- rameters during luteal and follicular phase of menstrual cycle in pubertal girls but this difference was found statistical significant only with FEV1/FVC (%). Conclusion: Respiratory parameters during phases of sexual cycle in pubertal girls, the results of which shows slight changes and dif- ference was statistically not significant except FEV1/FVC (%).